The potential of single-cell profiling in plants. Issue 1 (December 2016) - Efroni, Idan; Birnbaum, Kenneth
Abstract Single-cell transcriptomics has been employed in a growing number of animal studies, but the technique has yet to be widely used in plants. Nonetheless, early studies indicate that single-cell RNA-seq protocols developed for animal cells produce informative datasets in plants. We argue that single-cell transcriptomics has the potential to provide a new perspective on plant problems, such as the nature of the stem cells or initials, the plasticity of plant cells, and the extent of localized cellular responses to environmental inputs. Single-cell experimental outputs require different analytical approaches compared with pooled cell profiles and new tools tailored to single-cell assays are being developed. Here, we highlight promising new single-cell profiling approaches, their limitations as applied to plants, and their potential to address fundamental questions in plant biology.